Effect of Yoga Exercise on Cortisol Hormone Levels in Pregnant Women in Kinik Pratama Asih Waluyojati Banguntapan Bantul Yogyakarta - Ratih Kumorojati; Alfie Alfie; Agus Warseno (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2020)
Maternal mortality rates in 2016 rose compared to 2015. The causes of maternal death in 2016 were Severe Preeclampsia (PEB) as much as 33% (4 cases), Bleeding by 17% (2 cases), Heart Failure 17% (2 cases), Sepsis 17% (2 cases) and Other 16% (2 cases). Some studies state that preeclampsia occurs due to the influence of anxiety during pregnancy. Pregnancy is a period of crisis that involves also psychological factors, hormonal changes causing the mother's emotions to become lame. In addition to physical factors, psycho social factors can add anxiety in pregnant women. High stress in pregnancy can increase stress hormones, it can also lead to increased blood pressure and birth weight loss. Prevention can be done by pregnant women to have a healthy condition both the mother and her fetus, as well as through the normal labor process that is by exercising, gymnastics, dancing, and yoga. At this time yoga becomes one of the self help that can support the process of pregnancy, birth. Physiological of yoga performed during pregnancy is reversing the effects of stress involving the parasympathetic part of the central nervous system. The effects of such stress will be inhibited by relaxation, so that the hormones that cause body dysregulation (cortisol) will be reduced in number. The hormone cortisol is an increased hormone in anxiety so by masterminding this hormone can lower the anxiety levels of pregnant women which has an impact on the decreased risk of PEB. Look at the effect of Yoga exercise on cortisol hormone levels in pregnant women. This type of quantitative research is True Experimental research method, with Posttest-Only Control Group Design. Respondents who used pregnant women who participated in prenatal yoga, samples taken with the Formula Freeder obtained 16 pregnant women with control as many as 16. Data analysis was performed using the Pearson Chi-Square test with a result of p <0.00 which indicates a correlation. There is an effect of yoga on cortisol levels in pregnant women.